Cobalt oxyhydroxide-cobalt sesquioxide composite, cobalt sesquioxide, and preparation method thereof, lithium cobaltate, lithium battery, and lithium device

CN116632228BActive Publication Date: 2026-10-16HUNAN ZOOMWE NEW ENERGY TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310651060.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2026-10-16
Estimated Expiration
2043-06-02

AI Technical Summary

Benefits of technology

[0049] (1) Compared with pure cobalt hydroxyl oxide prepared by liquid phase method, the cobalt hydroxyl oxide-cobalt tetroxide composite material provided in this application has plate-shaped cobalt hydroxyl oxide as the skeleton, and multiple cobalt tetroxide primary particles fill the gaps formed between multiple cobalt hydroxyl oxide particles. The porosity is low, the tap density is high, and the particle size distribution is wide. This can improve the compaction density of lithium cobalt oxide, the cathode material that inherits this structure, thereby improving the battery capacity of lithium-ion batteries and meeting the long battery life requirements of smart wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116632228B_ABST
    Figure CN116632228B_ABST
Patent Text Reader

Abstract

The application provides a cobalt oxyhydroxide-cobalt sesquioxide composite material, a cobalt sesquioxide, a preparation method of the cobalt oxyhydroxide-cobalt sesquioxide composite material, lithium cobaltate, a lithium battery and a lithium battery device, and relates to the field of lithium ion batteries. The secondary particles of the composite material comprise a plurality of cobalt sesquioxide primary particles and a plurality of cobalt oxyhydroxide primary particles, and the plurality of cobalt sesquioxide primary particles are filled in the gaps formed between the plurality of cobalt oxyhydroxide primary particles. The preparation method comprises the following steps: adding cobalt liquid, a precipitating agent, an oxidizing agent and a complexing agent into a bottom liquid, and obtaining cobalt oxyhydroxide-cobalt sesquioxide slurry through reaction, and then performing solid-liquid separation to obtain the cobalt oxyhydroxide-cobalt sesquioxide composite material. The cobalt sesquioxide raw material comprises the cobalt oxyhydroxide-cobalt sesquioxide composite material. The lithium cobaltate raw material comprises the cobalt sesquioxide and a lithium source. The lithium battery raw material comprises the lithium cobaltate. The cobalt oxyhydroxide-cobalt sesquioxide composite material provided by the application has high compaction density, and the prepared lithium battery has large capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion batteries, and in particular to a cobalt hydroxyl oxide-cobalt tetroxide composite material, cobalt tetroxide and its preparation method, lithium cobalt oxide, lithium batteries and lithium battery devices. Background Technology

[0002] With the increasingly frequent updates and replacements of 3C products, "lighter, thinner, and more durable" is a development trend. Compared with mobile phone batteries, devices such as headphones, smart bracelets, smartwatches, e-cigarettes, smart glasses, and smart sports shoes have higher requirements for battery capacity in order to achieve the requirements of "small size, lightness, thinness, and long battery life".

[0003] Therefore, improving the volumetric energy density of cathode materials and cathode material precursors, which contribute the most to the battery capacity of lithium batteries, is a key research focus in this industry. Summary of the Invention

[0004] The purpose of this application is to provide a cobalt hydroxyoxide-cobalt tetroxide composite material, cobalt tetroxide and its preparation method, lithium cobalt oxide, lithium battery and lithium battery device to solve the above problems.

[0005] To achieve the above objectives, this application adopts the following technical solution:

[0006] A cobalt hydroxyl oxide-cobalt tetroxide composite material, wherein the secondary particles of the cobalt hydroxyl oxide-cobalt tetroxide composite material include multiple primary cobalt tetroxide particles and multiple primary cobalt hydroxyl oxide particles, wherein the multiple primary cobalt tetroxide particles fill the gaps formed between the multiple cobalt hydroxyl oxide particles.

[0007] Preferably, the cobalt hydroxyl oxide-cobalt tetroxide composite material satisfies at least one of the following conditions:

[0008] A. In the cobalt hydroxyoxide-cobalt tetroxide composite material, cobalt tetroxide has a spinel structure;

[0009] B. The primary cobalt hydroxyoxide particles in the cobalt hydroxyoxide-cobalt tetroxide composite material are plate-shaped;

[0010] Preferably, the plate-shaped primary cobalt hydroxyl oxide particles are arranged in a disordered manner;

[0011] C. The molecular formula of the cobalt hydroxyoxide-cobalt tetroxide composite material is aCoOOH·bCo3O4, wherein the mass ratio of a to b is 2:8-8:2;

[0012] D. The secondary particles of the cobalt hydroxyl oxide-cobalt tetroxide composite material are spherical or near-spherical;

[0013] E. The particle size distribution (D90-D10) / (D90+D10) of the cobalt hydroxyl oxide-cobalt tetroxide composite material is 1.2-1.7;

[0014] F. The particle size D50 of the cobalt hydroxyoxide-cobalt tetroxide composite material is 3-16 μm;

[0015] Preferably, the particle size D50 of the cobalt hydroxyl oxide-cobalt tetroxide composite material is 3-10 μm;

[0016] The tap density of the G. cobalt hydroxyl oxide-cobalt tetroxide composite material is 2.8-3.4 g / cm³. 3 .

[0017] This application also provides a cobalt tetroxide, wherein the raw material for cobalt tetroxide includes a cobalt hydroxyl oxide-cobalt tetroxide composite material.

[0018] Preferably, cobalt tetroxide satisfies at least one of the following conditions:

[0019] H. The particle size distribution (D90-D10) / (D90+D10) of cobalt tetroxide is 1.2-1.7;

[0020] I. The particle size D50 of cobalt tetroxide is 3-16 μm;

[0021] Preferably, the particle size D50 of cobalt tetroxide is 3-10 μm;

[0022] J. The tap density of cobalt tetroxide is 2.8-3.4 g / cm³. 3 ;

[0023] K. The overall average pore size of cobalt tetroxide is 20-120 nm;

[0024] L. The overall porosity of cobalt tetroxide is 3-10%;

[0025] The specific surface area of ​​M. cobalt tetroxide is 1.7-4.5 m². 2 / g.

[0026] This application also provides a method for preparing a cobalt hydroxyl oxide-cobalt tetroxide composite material, comprising:

[0027] A solution including cobalt solution, precipitant, oxidant and complexing agent is added to the bottom liquid. After reaction, cobalt hydroxyl oxide-cobalt tetroxide slurry is obtained. Solid-liquid separation yields cobalt hydroxyl oxide-cobalt tetroxide composite material.

[0028] Preferably, the preparation method of the cobalt hydroxyl oxide-cobalt tetroxide composite material satisfies at least one of the following conditions:

[0029] a. The cobalt solution includes aqueous cobalt chloride solution and / or aqueous cobalt sulfate solution, wherein the mass concentration of cobalt ions in the cobalt solution is 90-130 g / L;

[0030] b. The precipitant includes an aqueous solution of sodium hydroxide;

[0031] c. Complexing agents include EDTA-2Na and / or ammonia;

[0032] d. Oxidizing agents include one or more of air, oxygen, and hydrogen peroxide with a volume fraction of 10-30%;

[0033] Preferably, the air is compressed air, and the flow rate of the compressed air is 200-1000% / h of the usable volume of the reaction vessel; the flow rate of oxygen is 40-200% / h of the usable volume of the reaction vessel; and the flow rate of hydrogen peroxide is 0.5-4% / h of the usable volume of the reaction vessel.

[0034] f. The base solution consists of a precipitant and water, and the pH of the base solution is 10-12;

[0035] g. The amount of the base liquid should be 5-50% of the usable volume of the reaction vessel;

[0036] h. The pH of the reaction is 9-12, and the reaction temperature is 50-80℃;

[0037] i. The flow rate of the cobalt solution is 0.5-8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 2-6% / h of the available volume of the reaction vessel;

[0038] j. The cobalt solution also includes dopant compounds, and the dopant elements include one or more of Al, Zr, Ti, Mg, Y, La, W, Ni, and Mn.

[0039] A method for preparing cobalt tetroxide, comprising sintering the cobalt hydroxyl oxide-cobalt tetroxide composite material prepared above.

[0040] This application also provides a lithium cobalt oxide, wherein the raw materials for the lithium cobalt oxide include a lithium source, and the above-mentioned cobalt hydroxyl oxide-cobalt tetroxide and / or the above-mentioned cobalt tetroxide.

[0041] Preferably, lithium cobalt oxide satisfies at least one of the following conditions:

[0042] k. The molar ratio of the sum of the molar amounts of cobalt and doping elements in cobalt tetroxide to the molar amount of lithium in the lithium source is 1:(1.02-1.06);

[0043] 1. Lithium cobalt oxide is obtained from lithium cobalt oxide raw materials through a first sintering and a second sintering process;

[0044] m. When condition l is met, the first sintering includes: heating the lithium cobalt oxide raw material from room temperature to 600℃-900℃, holding it at that temperature for 2h-10h, then heating it to 900℃-1150℃, holding it at that temperature for 5h-20h, and then cooling it.

[0045] The second sintering process includes: heating the material obtained from the first sintering from room temperature to 900℃-1100℃, holding it at that temperature for 5h-20h, and then cooling it.

[0046] This application also provides a lithium battery, the raw material of which includes lithium cobalt oxide.

[0047] This application also provides a lithium battery device, including a lithium battery.

[0048] Compared with the prior art, the beneficial effects of this application include:

[0049] (1) Compared with pure cobalt hydroxyl oxide prepared by liquid phase method, the cobalt hydroxyl oxide-cobalt tetroxide composite material provided in this application has plate-shaped cobalt hydroxyl oxide as the skeleton, and multiple cobalt tetroxide primary particles fill the gaps formed between multiple cobalt hydroxyl oxide particles. The porosity is low, the tap density is high, and the particle size distribution is wide. This can improve the compaction density of lithium cobalt oxide, the cathode material that inherits this structure, thereby improving the battery capacity of lithium-ion batteries and meeting the long battery life requirements of smart wearable devices.

[0050] (2) Compared with the cobalt hydroxyl oxide-cobalt tetroxide product (cobalt hydroxyl oxide:cobalt tetroxide mass ratio <2:8) or pure cobalt tetroxide product prepared by liquid phase method with excessive cobalt tetroxide content, the cobalt hydroxyl oxide-cobalt tetroxide composite material claimed in this application is spherical or near-spherical. When the primary cobalt hydroxyl oxide particles, which serve as the skeleton, are transformed into primary cobalt tetroxide particles during the sintering process, the shrinkage of the secondary particle size D50 is very small. This can form a certain amount of pores with moderate size and relatively uniform distribution between the primary particles, which is beneficial for lithium carbonate to enter during the sintering of the cathode material and maintain a certain reactivity with lithium carbonate. Attached Figure Description

[0051] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0052] Figure 1 A schematic diagram of the theoretical structure of the cobalt hydroxyl oxide-cobalt tetroxide composite material provided in this application;

[0053] Figure 2 This is a magnified SEM image of the surface of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 1;

[0054] Figure 3 Here is a cross-sectional SEM image of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 1;

[0055] Figure 4 The XRD pattern of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 1 is shown below.

[0056] Figure 5 Here is a surface SEM image of cobalt tetroxide obtained in Example 1;

[0057] Figure 6 This is a magnified SEM image of the surface of cobalt tetroxide obtained in Example 1;

[0058] Figure 7 Here is a cross-sectional SEM image of cobalt tetroxide obtained in Example 1;

[0059] Figure 8 This is a magnified SEM image of the surface of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 2;

[0060] Figure 9 Here is a cross-sectional SEM image of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 2;

[0061] Figure 10 Here is a surface SEM image of cobalt tetroxide obtained in Example 2;

[0062] Figure 11 This is a magnified SEM image of the surface of cobalt tetroxide obtained in Example 2;

[0063] Figure 12 This is a magnified SEM image of a cross-section of cobalt tetroxide obtained in Example 2;

[0064] Figure 13 Here is a surface SEM image of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 3;

[0065] Figure 14 Here is a surface SEM image of cobalt tetroxide obtained in Example 3;

[0066] Figure 15 This is a magnified SEM image of the surface of cobalt tetroxide obtained in Example 3;

[0067] Figure 16 Here is a cross-sectional SEM image of cobalt tetroxide obtained in Example 3;

[0068] Figure 17 This is a magnified SEM image of the surface of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 4;

[0069] Figure 18 Here is a surface SEM image of cobalt tetroxide obtained in Example 4;

[0070] Figure 19 This is a magnified SEM image of the surface of cobalt tetroxide obtained in Example 4;

[0071] Figure 20 This is a magnified SEM image of the surface of cobalt carbonate obtained in Comparative Example 1.

[0072] Figure 21 Here is a surface SEM image of cobalt tetroxide obtained in Comparative Example 1;

[0073] Figure 22 The image shows a cross-sectional SEM image of cobalt tetroxide obtained in Comparative Example 1.

[0074] Figure 23 This is a magnified SEM image of the surface of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in control group 1.

[0075] Figure 24 This is a magnified SEM image of the surface of cobalt tetroxide obtained from control group 1.

[0076] Figure 25 This is a magnified SEM image of the surface of cobalt hydroxyl oxide obtained from control group 2.

[0077] Figure 26 Here is a surface SEM image of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Comparative Example 2;

[0078] Figure 27 The image shows the XRD pattern of the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained in Example 1. Detailed Implementation

[0079] First, the technical solution provided in this application will be described in general as follows:

[0080] A cobalt hydroxyl oxide-cobalt tetroxide composite material, wherein the secondary particles of the cobalt hydroxyl oxide-cobalt tetroxide composite material include a plurality of primary cobalt tetroxide particles and a plurality of primary cobalt hydroxyl oxide particles, wherein the plurality of primary cobalt tetroxide particles fill the gaps formed between the plurality of cobalt hydroxyl oxide particles.

[0081] It should be noted that "multiple" is used to indicate two or more.

[0082] Its theoretical structure diagram is as follows Figure 1 As shown.

[0083] It should be noted that the cobalt hydroxyl oxide-cobalt tetroxide composite material itself is a secondary particle composed of multiple primary particles.

[0084] In an optional embodiment, the cobalt hydroxyl oxide-cobalt tetroxide composite material satisfies at least one of the following conditions:

[0085] A. In the cobalt hydroxyoxide-cobalt tetroxide composite material, cobalt tetroxide has a spinel structure;

[0086] B. The primary cobalt hydroxyoxide particles in the cobalt hydroxyoxide-cobalt tetroxide composite material are plate-shaped;

[0087] Preferably, the plate-shaped primary cobalt hydroxyl oxide particles are arranged in a disordered manner;

[0088] C. The molecular formula of the cobalt hydroxyoxide-cobalt tetroxide composite material is aCoOOH·bCo3O4, wherein the mass ratio of a to b is 2:8-8:2;

[0089] If the cobalt tetroxide content in the cobalt hydroxyl oxide-cobalt tetroxide composite material is too high, the cobalt tetroxide will be too dense after sintering, resulting in a low overall average pore size and overall porosity. This will lead to low sintering reaction activity, poor crystal development, and fine grains when sintering into a cathode material, which is not conducive to the penetration reaction of electrolyte and results in poor battery capacity. Furthermore, the overall structure of the secondary particles will be poor, not being individual spherical or near-spherical, making the sintered cathode material prone to cracking during charge and discharge, and reducing cycle performance. On the other hand, if the cobalt hydroxyl oxide content is too high, the secondary particles will be relatively loose and have low density, resulting in a high overall average pore size and overall porosity, and a low tap density. This will also lead to a low compaction density in the resulting cathode material, ultimately affecting battery capacity. By limiting the mass ratio of cobalt hydroxyl oxide to cobalt tetroxide to a certain extent, the secondary particles have a dense spherical or near-spherical structure, which improves both the battery capacity and cycle performance of cobalt tetroxide and lithium cobalt oxide. In addition, the pore distribution of the sintered cobalt tetroxide is uniform, which improves the reaction activity of the cathode sintering, reduces the sintering temperature, and thus reduces energy consumption.

[0090] Optionally, the mass ratio of a to b can be any value between 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, or 2:8-8:2;

[0091] D. The secondary particles of the cobalt hydroxyl oxide-cobalt tetroxide composite material are spherical or near-spherical;

[0092] E. The particle size distribution (D90-D10) / (D90+D10) of the cobalt hydroxyl oxide-cobalt tetroxide composite material is 1.2-1.7;

[0093] A wider particle size distribution can effectively improve the compaction density of the cathode material, thereby further improving the energy density of the lithium battery;

[0094] Optionally, the particle size distribution (D90-D10) / (D90+D10) of the cobalt hydroxyl oxide-cobalt tetroxide composite material can be any value between 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or 1.2-1.7; the particle size D50 of the composite material can be any value between 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm or 3-16μm.

[0095] F. The particle size D50 of the cobalt hydroxyoxide-cobalt tetroxide composite material is 3-16 μm;

[0096] In a preferred embodiment, the particle size D50 of the cobalt hydroxyl oxide-cobalt tetroxide composite material is 3-10 μm;

[0097] The tap density of the G. cobalt hydroxyl oxide-cobalt tetroxide composite material is 2.8-3.4 g / cm³. 3 ;

[0098] Optionally, the tap density of the cobalt hydroxyl oxide-cobalt tetroxide composite material can be 2.8 g / cm³. 3 2.9g / cm 3 3.0g / cm 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 Or 2.8-3.4 g / cm³ 3 Any value between.

[0099] This application also provides a cobalt tetroxide, wherein the raw material for cobalt tetroxide includes a cobalt hydroxyl oxide-cobalt tetroxide composite material.

[0100] Preferably, cobalt tetroxide satisfies at least one of the following conditions:

[0101] H. The particle size distribution (D90-D10) / (D90+D10) of cobalt tetroxide is 1.2-1.7;

[0102] Optionally, the particle size distribution of cobalt tetroxide (D90-D10) / (D90+D10) can be any value between 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or 1.2-1.7; the particle size D50 of cobalt tetroxide can be any value between 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm or 3-16μm.

[0103] I. The particle size D50 of cobalt tetroxide is 3-16 μm;

[0104] In a preferred embodiment, the particle size D50 of cobalt tetroxide is 3-10 μm;

[0105] J. The tap density of cobalt tetroxide is 2.8-3.4 g / cm³. 3 ;

[0106] Optionally, the tap density of cobalt tetroxide can be 2.8 g / cm³. 3 2.9g / cm 3 3.0g / cm 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 Or 2.8-3.4 g / cm³ 3 Any value between;

[0107] K. The overall average pore size of cobalt tetroxide is 20-120 nm;

[0108] Optionally, the overall average pore size of cobalt tetroxide can be any value between 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, or 20-120nm.

[0109] The overall porosity of L. cobalt tetroxide is 3%-10%.

[0110] Optionally, the overall porosity of cobalt tetroxide can be any value between 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or 3%-10%.

[0111] In this application, the porosity and pore volume of cobalt tetroxide were tested using a fully automated specific surface area and pore size distribution analyzer (model: BELPREP-VACII / BELSORP-MINI-X) manufactured by Macchiato Inc., USA. The test principle was nitrogen adsorption method, and the specific test method was carried out in accordance with the instrument operating procedures and the accompanying workstation software provided by the manufacturer.

[0112] The specific surface area of ​​M. cobalt tetroxide is 1.7-4.5 m². 2 / g.

[0113] Optionally, the specific surface area of ​​cobalt tetroxide can be 1.7 m². 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m2 / g, 3.5m 2 / g, 4.0m 2 / g, 4.5m 2 / g or 1.7-4.5m 2 Any value between / g.

[0114] This application also provides a method for preparing a cobalt hydroxyl oxide-cobalt tetroxide composite material, comprising:

[0115] A solution including cobalt solution, precipitant, oxidant and complexing agent is added to the bottom liquid. After reaction, cobalt hydroxyl oxide-cobalt tetroxide slurry is obtained. Solid-liquid separation yields cobalt hydroxyl oxide-cobalt tetroxide composite material.

[0116] In an optional embodiment, the method for preparing the cobalt hydroxyl oxide-cobalt tetroxide composite material satisfies at least one of the following conditions:

[0117] a. The cobalt solution includes aqueous cobalt chloride solution and / or aqueous cobalt sulfate solution, wherein the mass concentration of cobalt ions in the cobalt solution is 90-130 g / L;

[0118] Optionally, the mass concentration of cobalt ions in the cobalt solution can be any value between 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, or 90-130 g / L.

[0119] b. The precipitant includes an aqueous solution of sodium hydroxide;

[0120] c. Complexing agents include EDTA-2Na and / or ammonia;

[0121] d. Oxidizing agents include one or more of air, oxygen, and hydrogen peroxide with a volume fraction of 10-30%;

[0122] Optionally, the volume fraction of hydrogen peroxide can be any value between 10%, 20%, 30%, or 10-30%.

[0123] In one optional embodiment, the air is compressed air, and the flow rate of the compressed air is 200-1000% / h of the available volume of the reaction vessel; the flow rate of oxygen is 40-200% / h of the available volume of the reaction vessel; and the flow rate of hydrogen peroxide is 0.5-4% / h of the available volume of the reaction vessel.

[0124] Optionally, the compressed air flow rate can be any value between 200% / h, 300% / h, 400% / h, 500% / h, 600% / h, 700% / h, 800% / h, 900% / h, 1000% / h, or 200-1000% / h of the available volume of the reaction vessel; the oxygen flow rate can be 40% / h, 60% / h, 80% / h, 100% / h, 120% / h, 140% / h, 160% / h, 180% / h, 200% / h, or [other values ​​not specified in the original text]. The flow rate of hydrogen peroxide can be any value between 40% and 200% / h; the flow rate of hydrogen peroxide can be any value between 0.5% / h, 0.6% / h, 0.8% / h, 1.0% / h, 1.2% / h, 1.4% / h, 1.6% / h, 1.8% / h, 2.0% / h, 2.2% / h, 2.4% / h, 2.6% / h, 2.8% / h, 3.0% / h, 3.2% / h, 3.4% / h, 3.6% / h, 3.8% / h, 4.0% / h, or 0.5%-4% / h of the available volume of the reaction vessel.

[0125] f. The base solution consists of a precipitant and water, and the pH of the base solution is 10-12;

[0126] Optionally, the pH of the base solution can be any value between 10, 11, 12, or 10-12;

[0127] g. The amount of the base liquid should be 5-50% of the usable volume of the reaction vessel;

[0128] Optionally, the amount of the base liquid can be any value between 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or 5-50% of the usable volume of the reaction vessel.

[0129] h. The pH of the reaction is 9-12, and the reaction temperature is 50-80℃;

[0130] Optionally, the pH of the reaction can be any value between 9, 10, 11, 12 or 9-12, and the temperature of the reaction can be any value between 50℃, 60℃, 70℃, 80℃ or 50-80℃.

[0131] i. The flow rate of the cobalt solution is 0.5-8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 2-6% / h of the available volume of the reaction vessel.

[0132] Optionally, the flow rate of the cobalt solution can be any value between 0.5% / h, 0.1% / h, 2% / h, 3% / h, 4% / h, 5% / h, 6% / h, 7% / h, 8% / h or 0.5-8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent can be any value between 2% / h, 3% / h, 4% / h, 5% / h, 6% / h or 2-6% / h of the available volume of the reaction vessel.

[0133] j. The cobalt solution also includes dopant compounds, and the dopant elements include one or more of Al, Zr, Ti, Mg, Y, La, W, Ni, and Mn.

[0134] A method for preparing the above-mentioned cobalt tetroxide involves sintering the cobalt hydroxyl oxide-cobalt tetroxide composite material obtained above.

[0135] This application also provides a lithium cobalt oxide, wherein the raw materials for the lithium cobalt oxide include a lithium source, and the above-mentioned cobalt hydroxyl oxide-cobalt tetroxide and / or the above-mentioned cobalt tetroxide.

[0136] In an optional implementation, lithium cobalt oxide satisfies at least one of the following conditions:

[0137] k. The molar ratio of the sum of the molar amounts of cobalt and doping elements in cobalt tetroxide to the molar amount of lithium in the lithium source is 1:(1.02-1.06);

[0138] Optionally, the molar ratio of the sum of the molar amounts of cobalt in cobalt tetroxide and the dopant elements in the dopant compound to the lithium in the lithium source can be any value between 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06 or 1:(1.02-1.06).

[0139] 1. Lithium cobalt oxide is obtained from lithium cobalt oxide raw materials through a first sintering and a second sintering process;

[0140] m. When condition l is met, the first sintering includes: heating the lithium cobalt oxide raw material from room temperature to 600℃-900℃, holding it at that temperature for 2h-10h, then heating it to 900℃-1150℃, holding it at that temperature for 5h-20h, and then cooling it.

[0141] The second sintering process includes: heating the material obtained from the first sintering from room temperature to 900℃-1150℃, holding it at that temperature for 5h-20h, and then cooling it.

[0142] Optionally, during the first sintering process, the raw material is heated from room temperature to any value between 600℃, 700℃, 800℃, 900℃ or 600℃-900℃, and held at that temperature for 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or 2h-10h, and then heated to any value between 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃ or 900℃-1150℃, and held at that temperature for 5h, 10h, 15h, 20h or 5h-20h, and then cooled.

[0143] In the second sintering process, the material obtained from the first sintering is heated from room temperature to any value between 900℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃ or 900℃-1150℃, and held at that temperature for 5h, 10h, 15h, 20h or 5h-20h, and then cooled.

[0144] This application also provides a lithium battery, the raw material of which includes lithium cobalt oxide.

[0145] This application also provides a lithium battery device, including a lithium battery.

[0146] The lithium battery devices referred to in this application include devices that contain the lithium battery provided in this application, as well as devices that use the lithium battery provided in this application for power supply. Examples include smart wearable devices and electronic cigarettes.

[0147] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0148] Example 1

[0149] This embodiment provides a cobalt hydroxyl oxide-cobalt tetroxide composite material, the preparation method of which is as follows:

[0150] Step 1, prepare the solution: Prepare cobalt solution (cobalt chloride solution, cobalt content is 105g / L); precipitant (300g / L sodium hydroxide solution); complexing agent (2g / L EDTA-2Na solution); oxidant (compressed air).

[0151] Step 2, Synthesis Process: Stirring is started, and a precipitant and pure water are added to the reactor as a base solution (the base solution volume accounts for 25% of the usable reactor volume), with a pH of 11.8. Simultaneously, cobalt solution, precipitant, oxidant, and complexing agent are added to initiate the reaction. The cobalt solution flow rate is gradually reduced from 6% / h of the usable reactor volume to 3% / h, the complexing agent flow rate is 4% / h, and the compressed air flow rate is gradually reduced from 400% / h to 200% / h. The reaction temperature is 60℃, and the pH value is controlled between 10.6 and 11.0 by adjusting the precipitant flow rate. After the particle size D50 reaches 7.2 μm, the reaction is stopped, and the cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is collected.

[0152] Step 3, washing and drying: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, a wet cobalt hydroxyl oxide-cobalt tetroxide mixture is obtained. The dehydrated wet cobalt hydroxyl oxide-cobalt tetroxide mixed phase mixture is then transferred to an oven for drying at 120℃ for 12 hours.

[0153] The surface SEM magnification and cross-sectional SEM images of the obtained cobalt hydroxyl oxide-cobalt tetroxide composite material are shown below. Figure 2 and Figure 3 As shown, the XRD pattern is as follows Figure 4 As shown. Among them, from Figure 2 and Figure 3 As can be seen from the XRD, the primary cobalt hydroxyl oxide particles are plate-shaped and relatively large, forming a framework; the primary cobalt tetroxide particles are smaller; multiple primary cobalt tetroxide particles fill the gaps formed between the multiple plate-shaped cobalt hydroxyl oxide particles; the XRD shows that cobalt tetroxide has a spinel structure, and the mass ratio of cobalt hydroxyl oxide to cobalt tetroxide is approximately 4.1:5.9. The mass ratio of cobalt hydroxyl oxide to cobalt tetroxide was calculated using the built-in analytical calculation function of the XRD analysis software. The same applies below.

[0154] This embodiment provides a cobalt tetroxide, which is based on the above-obtained cobalt hydroxyl oxide-cobalt tetroxide composite material and the following operations are performed:

[0155] Step 4, sintering: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase is sintered in a rotary kiln for 2 hours at a sintering temperature of 730℃ to obtain cobalt tetroxide.

[0156] The obtained surface SEM images of cobalt tetroxide are as follows: Figure 5 As shown in the enlarged partial photograph, Figure 6 As shown; the SEM image of the cross-section of the obtained cobalt tetroxide is as follows. Figure 7 As shown. From Figure 6-7As can be seen from the figure: no large plate-shaped cobalt hydroxyl oxide primary particles were found, meaning that the plate-shaped cobalt hydroxyl oxide has been completely sintered into cobalt tetroxide; the primary particles have relatively large and uniform grains with good grain development; and there are also a certain amount of pores with moderate pore size between the primary particles.

[0157] Example 2

[0158] This embodiment provides a cobalt hydroxyl oxide-cobalt tetroxide composite material, the preparation method of which is as follows:

[0159] Step 1, prepare the solution: prepare cobalt solution (cobalt sulfate solution, cobalt content is 90g / L); precipitant (300g / L sodium hydroxide solution); complexing agent (10g / L ammonia solution); oxidant (15% hydrogen peroxide by mass).

[0160] Step 2, Synthesis Process: Stirring is started, and a precipitant and pure water are added to the reactor as a base solution (the base solution volume accounts for 10% of the usable reactor volume), with a pH of 11.0. Simultaneously, cobalt solution, precipitant, oxidant, and complexing agent are added to initiate the reaction. The cobalt solution flow rate is gradually reduced from 3% / h of the usable reactor volume to 1.5% / h, the complexing agent flow rate is 4% / h, and the oxidant flow rate is gradually reduced from 2% / h to 1% / h. The reaction temperature is 50℃, and the reaction pH is controlled to 9.6-10.0 by adjusting the precipitant flow rate. After the particle size D50 reaches 6.5μm, the reaction is stopped, and the cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is collected.

[0161] Step 3, washing and drying: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, a wet cobalt hydroxyl oxide-cobalt tetroxide mixture is obtained. The dehydrated wet cobalt hydroxyl oxide-cobalt tetroxide mixed phase mixture is then transferred to an oven for drying at 120℃ for 12 hours.

[0162] A magnified SEM image of the obtained cobalt hydroxyl oxide-cobalt tetroxide composite surface is shown below. Figure 8 As shown, the cross-sectional SEM image is as follows: Figure 9 As shown. From Figure 8-9 It can be seen that the primary cobalt hydroxyl oxide particles are plate-shaped and relatively large, forming a framework; the primary cobalt tetroxide particles are smaller; multiple primary cobalt tetroxide particles fill the gaps formed between multiple plate-shaped cobalt hydroxyl oxide particles. The mass ratio of cobalt hydroxyl oxide to cobalt tetroxide is approximately 4.5:5.5.

[0163] This embodiment provides a cobalt tetroxide, which is based on the above-obtained cobalt hydroxyl oxide-cobalt tetroxide composite material and the following operations are performed:

[0164] Step 4, sintering: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase is sintered in a rotary kiln for 2 hours at a sintering temperature of 730℃ to obtain cobalt tetroxide.

[0165] The obtained surface SEM images of cobalt tetroxide are as follows: Figure 10 As shown in the enlarged partial photograph, Figure 11 As shown; the SEM image of the cross-section of the obtained cobalt tetroxide is as follows. Figure 11 As shown in the enlarged partial photograph, Figure 12 As shown. From Figure 11-12 As can be seen from the figure: no large plate-shaped cobalt hydroxyl oxide primary particles were found, meaning that the plate-shaped cobalt hydroxyl oxide has been completely sintered into cobalt tetroxide; the primary particles have relatively large and uniform grains with good grain development; and there are also a certain amount of pores with moderate pore size between the primary particles.

[0166] Example 3

[0167] This embodiment provides a cobalt hydroxyl oxide-cobalt tetroxide composite material, the preparation method of which is as follows:

[0168] Step 1, prepare the solution: prepare cobalt solution (cobalt chloride solution, cobalt content is 130g / L); precipitant (450g / L sodium hydroxide solution); complexing agent (2g / L EDTA-2Na solution); oxidant (compressed air).

[0169] Step 2, Synthesis Process: Stirring is started, and a precipitant and pure water are added to the reactor as a base solution (the base solution volume accounts for 50% of the usable reactor volume), with a pH of 12.0. Simultaneously, cobalt solution, precipitant, oxidant, and complexing agent are added to initiate the reaction. The cobalt solution flow rate is gradually reduced from 8% / h of the usable reactor volume to 4% / h, the complexing agent flow rate is 4% / h, and the oxygen flow rate is gradually reduced from 120% / h to 60% / h. The reaction temperature is 60℃, and the reaction pH is controlled to 10.2-10.6 by adjusting the precipitant flow rate. After the particle size D50 reaches 4.1 μm, the reaction is stopped, and the cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is collected.

[0170] Step 3, washing and drying: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, a wet cobalt hydroxyl oxide-cobalt tetroxide mixture is obtained. The dehydrated wet cobalt hydroxyl oxide-cobalt tetroxide mixed phase mixture is then transferred to an oven for drying at 120℃ for 12 hours.

[0171] The surface SEM images of the obtained cobalt hydroxyl oxide-cobalt tetroxide composite material are as follows: Figure 13 As shown. From Figure 13It can be seen that: the primary particles of cobalt hydroxyoxide are plate-shaped and relatively large, serving as the framework; the primary particles of cobalt tetroxide are smaller; multiple primary particles of cobalt tetroxide fill the gaps formed between multiple plate-shaped cobalt hydroxyoxide particles; and the mass ratio of cobalt hydroxyoxide to cobalt tetroxide is approximately 6.4:3.6.

[0172] This embodiment provides a cobalt tetroxide, which is based on the above-obtained cobalt hydroxyl oxide-cobalt tetroxide composite material and the following operations are performed:

[0173] Step 4, sintering: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase is sintered in a rotary kiln for 2 hours at a sintering temperature of 700℃ to obtain cobalt tetroxide.

[0174] The obtained surface SEM images of cobalt tetroxide are as follows: Figure 14 As shown in the enlarged partial photograph, Figure 15 As shown; the SEM image of the cross-section of the obtained cobalt tetroxide is as follows. Figure 16 As shown. From Figure 15-16 As can be seen from the figure: no large plate-shaped cobalt hydroxyl oxide primary particles were found, meaning that the plate-shaped cobalt hydroxyl oxide has been completely sintered into cobalt tetroxide; the primary particles have relatively large and uniform grains with good grain development; and there are also a certain amount of pores with moderate pore size between the primary particles.

[0175] Example 4

[0176] This embodiment provides a cobalt hydroxyl oxide-cobalt tetroxide composite material, the preparation method of which is as follows:

[0177] Step 1, prepare the solution: prepare cobalt solution (cobalt chloride solution, cobalt content is 130g / L); precipitant (400g / L sodium hydroxide solution); complexing agent (2g / L EDTA-2Na solution); oxidant (compressed air).

[0178] Step 2, Synthesis Process: Start stirring and add a precipitant and pure water as a base solution (the base solution volume accounts for 20% of the usable volume of the reactor), with a pH of 11.8. Simultaneously add cobalt solution, precipitant, and oxidant to initiate the reaction. The cobalt solution flow rate is gradually reduced from 8% / h of the usable reactor volume to 4% / h, the complexing agent flow rate is 4% / h, and the compressed air flow rate is gradually reduced from 800% / h to 400% / h. The reaction temperature is 60℃, and the pH value is controlled to 10.2-10.6 by adjusting the precipitant flow rate. After the particle size D50 reaches 8.3μm, the reaction is stopped, and the cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is collected.

[0179] Step 3, washing and drying: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, a wet cobalt hydroxyl oxide-cobalt tetroxide mixture is obtained. The dehydrated wet cobalt hydroxyl oxide-cobalt tetroxide mixed phase mixture is then transferred to an oven for drying at 120℃ for 12 hours.

[0180] A magnified SEM image of the obtained cobalt hydroxyl oxide-cobalt tetroxide composite surface is shown below. Figure 17 As shown. From Figure 17 As can be seen, the primary cobalt hydroxyl oxide particles are plate-shaped and relatively large, forming a framework; the primary cobalt tetroxide particles are smaller; multiple primary cobalt tetroxide particles fill the gaps formed between multiple plate-shaped cobalt hydroxyl oxide particles. The mass ratio of cobalt hydroxyl oxide to cobalt tetroxide is approximately 3.0:7.0.

[0181] This embodiment provides a cobalt tetroxide, which is based on the above-obtained cobalt hydroxyl oxide-cobalt tetroxide composite material and the following operations are performed:

[0182] Step 4, sintering: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase is sintered in a rotary kiln for 2 hours at a sintering temperature of 743℃ to obtain cobalt tetroxide.

[0183] The obtained surface SEM images of cobalt tetroxide are as follows: Figure 18 As shown in the enlarged partial photograph, Figure 19 As shown. From Figure 19 As can be seen from the figure: no large plate-shaped cobalt hydroxyl oxide primary particles were found, meaning that the plate-shaped cobalt hydroxyl oxide has been completely sintered into cobalt tetroxide; the primary particles have relatively large and uniform grains with good grain development; and there are also a certain amount of pores with moderate pore size between the primary particles.

[0184] Example 5

[0185] This embodiment provides a cobalt hydroxyl oxide-cobalt tetroxide composite material, the preparation method of which is as follows:

[0186] Step 1, prepare the solution: Prepare an aluminum-doped cobalt solution (cobalt solution containing cobalt chloride and aluminum sulfate, with a cobalt content of 105 g / L and an Al content of 1.47 g / L); a precipitant (300 g / L sodium hydroxide solution); a complexing agent (2 g / L EDTA-2Na solution); and an oxidizing agent (compressed air).

[0187] Step 2, Synthesis Process: Stirring is started, and a precipitant and pure water are added to the reactor as a base solution (the base solution volume accounts for 25% of the usable reactor volume), with a pH of 11.5. Simultaneously, cobalt solution, precipitant, oxidant, and complexing agent are added to initiate the reaction. The cobalt solution flow rate is gradually reduced from 6% / h of the usable reactor volume to 3% / h, the complexing agent flow rate is 4% / h, and the compressed air flow rate is gradually reduced from 400% / h to 200% / h. The reaction temperature is 60℃, and the reaction pH is controlled to 10.6-11.0 by adjusting the precipitant flow rate. After the particle size D50 reaches 7.0 μm, the reaction is stopped, and the aluminum-doped cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is collected.

[0188] Step 3, washing and drying: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, a wet cobalt hydroxyl oxide-cobalt tetroxide mixture is obtained. The dehydrated wet cobalt hydroxyl oxide-cobalt tetroxide mixture is then transferred to an oven for drying at 120℃ for 12 hours. The mass ratio of cobalt hydroxyl oxide to cobalt tetroxide is approximately 5.5:4.5.

[0189] This embodiment provides an aluminum-doped cobalt tetroxide, which is based on the above-obtained aluminum-doped cobalt hydroxyl oxide-cobalt tetroxide composite material, and the following operations are performed:

[0190] Step 4, sintering: The aluminum-doped cobalt hydroxyl oxide-cobalt tetroxide mixed phase is sintered in a rotary kiln for 2 hours at a sintering temperature of 745℃ to obtain aluminum-doped cobalt tetroxide.

[0191] Comparative Example 1

[0192] This comparative example provides a cobalt carbonate, the preparation method of which is as follows:

[0193] Step 1, prepare the solution: prepare cobalt solution (cobalt sulfate solution, cobalt content is 120g / L), and prepare precipitant (220g / L ammonium bicarbonate solution).

[0194] Step 2, Synthesis Process: Start stirring and add pure water as a base liquid (20% of the usable reactor volume) to the reactor. Heat to 45°C and simultaneously start the cobalt solution and precipitant feed pumps. The cobalt solution flow rate is 3% / h of the usable reactor volume. Control the reaction pH to 7.1 by adjusting the precipitant flow rate to carry out the cobalt carbonate precipitation reaction until the reactor slurry reaches 90% of the usable reactor volume. Turn off stirring and wait for solid-liquid separation. Then, start the feed pump and repeat the above feeding and supernatant extraction operations until the particle size D50 reaches 7.3 μm. Stop the reaction and collect the cobalt carbonate slurry.

[0195] Step 3, washing and drying: The cobalt carbonate slurry is discharged and transferred to a centrifuge for dehydration and washing to obtain large-particle wet cobalt carbonate. After dehydration, the large-particle wet cobalt carbonate is transferred to an oven for drying at 120℃ for 12 hours.

[0196] The obtained SEM magnified images of the cobalt carbonate surface are as follows: Figure 20 As shown. From Figure 20 As can be seen, the primary cobalt carbonate particles are densely stacked in a cubic shape.

[0197] This embodiment provides a cobalt tetroxide, which is obtained by performing the following operations based on the cobalt carbonate obtained above:

[0198] Step 4, sintering: The dried cobalt carbonate is transferred to a rotary kiln for sintering at a high temperature of 700℃ for 2 hours to produce cobalt tetroxide.

[0199] The obtained surface SEM images of cobalt tetroxide are as follows: Figure 21 As shown; the obtained SEM image of the cross-section of cobalt tetroxide is as follows. Figure 22 As shown. From Figure 22 As can be seen from the figure: no large plate-shaped primary cobalt carbonate particles were found, that is, the plate-shaped cobalt carbonate has been completely sintered into cobalt tetroxide; the primary particles have larger and more uniform grains, and the grain development is better; however, the porosity and pore size between the primary particles are larger than those in Examples 1-5.

[0200] Control group 1

[0201] This control group 1 provides a cobalt hydroxyl oxide-cobalt tetroxide composite material, the preparation method of which is as follows:

[0202] Step 1, prepare the solution: prepare cobalt solution (cobalt chloride solution, cobalt content is 130g / L); precipitant (400g / L sodium hydroxide solution); complexing agent (10g / L ammonia solution); oxidant (compressed air).

[0203] Step 2, Synthesis Process: Stirring is started, and a precipitant and pure water are added to the reactor as a base solution (the base solution volume accounts for 20% of the usable reactor volume), with a pH of 12.8. Simultaneously, cobalt solution, precipitant, oxidant, and complexing agent are added to initiate the reaction. The cobalt solution flow rate is 2% / h of the usable reactor volume, the complexing agent flow rate is 4% / h, the compressed air flow rate is 1600% / h, and the reaction temperature is 40℃. The reaction pH is controlled to 12.0-12.4 by adjusting the precipitant flow rate. The reaction is stopped when the particle size D50 reaches 4.2 μm, and the hydroxyl cobalt oxide-cobalt tetroxide mixed phase slurry is collected.

[0204] Step 3, washing and drying: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, a wet cobalt hydroxyl oxide-cobalt tetroxide mixture is obtained. The dehydrated wet cobalt hydroxyl oxide-cobalt tetroxide mixed phase mixture is then transferred to an oven for drying at 120℃ for 12 hours.

[0205] A magnified SEM image of the obtained cobalt hydroxyl oxide-cobalt tetroxide composite surface is shown below. Figure 23 As shown. From Figure 23 It can be seen that the primary particles of cobalt hydroxyl oxide are plate-shaped and relatively large, serving as a framework; the primary particles of cobalt tetroxide are smaller; a small amount of cobalt tetroxide primary particles are attached to the surface of multiple plate-shaped cobalt hydroxyl oxide particles. The mass ratio of cobalt hydroxyl oxide to cobalt tetroxide is approximately 8.9:1.1.

[0206] This embodiment provides a cobalt tetroxide, which is based on the above-obtained cobalt hydroxyl oxide-cobalt tetroxide composite material and the following operations are performed:

[0207] Step 4, sintering: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase is sintered in a rotary kiln for 3 hours at a sintering temperature of 700℃ to obtain cobalt tetroxide.

[0208] The obtained SEM magnified image of the cobalt tetroxide surface is as follows: Figure 24 As shown. From Figure 24 As can be seen from the figure: no large plate-shaped cobalt hydroxyl oxide was found, that is, all the plate-shaped cobalt hydroxyl oxide has been sintered into cobalt tetroxide; the primary particles have larger and more uniform grains, and the grain development is better; however, the porosity and pore size between the primary particles are larger than those in Examples 1-5.

[0209] Control group 2

[0210] This control group 2 provides a cobalt hydroxy oxide, which is prepared by the following method:

[0211] Step 1, prepare the solution: prepare cobalt solution (cobalt chloride solution, cobalt content is 130g / L); precipitant (400g / L sodium hydroxide solution); complexing agent (10g / L ammonia solution); oxidant (70g / L hydrogen peroxide with a mass fraction of 15%).

[0212] Step 2, Synthesis Process: Start stirring and add a precipitant and pure water as a base solution (the base solution volume accounts for 20% of the usable volume of the reactor), with a pH of 12.8. Simultaneously add cobalt solution, precipitant, oxidant, and complexing agent to initiate the reaction. The flow rates of the cobalt solution, complexing agent, and hydrogen peroxide are all 4% / h of the usable reactor volume. The reaction temperature is 40℃. The pH value is controlled between 11.8 and 12.2 by adjusting the precipitant flow rate. After the particle size D50 reaches 3.1 μm, the reaction is stopped, and the cobalt hydroxyl oxide slurry is collected.

[0213] Step 3, washing and drying: The cobalt hydroxyl oxide slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, wet cobalt hydroxyl oxide is obtained. The dehydrated wet cobalt hydroxyl oxide is then transferred to an oven for drying at 120°C for 12 hours.

[0214] The obtained SEM magnified image of the cobalt hydroxyl oxide surface is as follows: Figure 25 As shown. From Figure 25 As can be seen, the primary particles of cobalt hydroxyoxide are plate-shaped and arranged in an alternating pattern.

[0215] This embodiment provides a cobalt tetroxide, which is obtained by performing the following operations based on the above-described cobalt hydroxyl oxide:

[0216] Step 4, sintering: Cobalt hydroxyoxide is sintered in a rotary kiln for 2 hours at a temperature of 690℃ to obtain cobalt tetroxide.

[0217] Comparative Example 2

[0218] This comparative example provides a cobalt hydroxyl oxide-cobalt tetroxide composite material, the preparation method of which is as follows:

[0219] Step 1, prepare the solution: prepare cobalt solution (cobalt chloride solution, cobalt content is 130g / L); precipitant (400g / L sodium hydroxide solution); complexing agent (2g / L EDTA-2Na solution); oxidant (compressed air).

[0220] Step 2, Synthesis Process: Start stirring and add a precipitant and pure water as a base solution (the base solution volume accounts for 20% of the usable reactor volume), with a pH of 10.5. Simultaneously add cobalt solution, precipitant, oxidant, and complexing agent to initiate the reaction. The cobalt solution flow rate is 3% / h of the usable reactor volume, the complexing agent flow rate is 4% / h, the compressed air flow rate is 100% / h, the reaction temperature is 80℃, and the reaction pH is controlled to 9.2-9.6 by adjusting the precipitant flow rate. After the particle size D50 reaches 3.7μm, stop the reaction and collect the cobalt hydroxyl oxide-cobalt tetroxide mixed phase slurry.

[0221] Step 3, washing and drying: The cobalt hydroxyl oxide slurry is pumped into a centrifuge and rinsed with pure water. After centrifugation and dehydration, a wet cobalt hydroxyl oxide-cobalt tetroxide mixture is obtained. The dehydrated wet cobalt hydroxyl oxide-cobalt tetroxide mixture is then transferred to an oven for drying at 120°C for 12 hours.

[0222] The surface SEM images of the obtained cobalt hydroxyl oxide-cobalt tetroxide composite material are as follows: Figure 26 As shown, the XRD pattern is as follows Figure 27 As shown. From Figure 26 It can be seen that: no plate-shaped cobalt hydroxyl oxide primary particles are observed on the surface of the secondary particles; the surface of the secondary particles has multiple small cobalt tetroxide primary particles stacked on top of each other, with multiple grooves between the protrusions, making them prone to breakage. The mass ratio of cobalt hydroxyl oxide to cobalt tetroxide is approximately 0.9:9.1.

[0223] This embodiment provides a cobalt tetroxide, which is based on the above-obtained cobalt hydroxyl oxide-cobalt tetroxide composite material and the following operations are performed:

[0224] Step 4, sintering: The cobalt hydroxyl oxide-cobalt tetroxide mixed phase is sintered in a rotary kiln for 3 hours at a sintering temperature of 800℃ to obtain cobalt tetroxide.

[0225] Based on the cobalt tetroxide obtained in Examples 1-5, Control Groups 1-2, and Comparative Examples 1-2 above, lithium cobalt oxide was prepared by the following operations:

[0226] Lithium carbonate and cobalt tetroxide were mixed at a lithium to cobalt molar ratio of 1.05:1 and then sintered. The sintering process included a first sintering and a second sintering. The first sintering involved heating the material from room temperature to 800℃-1000℃, holding it at that temperature for 10 hours, then heating it to 900℃-1150℃, holding it at that temperature for 10 hours, and then cooling it. The second sintering involved heating the material obtained from the first sintering from room temperature to 1000℃-1200℃, holding it at that temperature for 12 hours, and then cooling it. Specific parameters are shown in Table 1 below.

[0227] The positive electrode materials prepared using cobalt tetroxide in Examples 1-5, Control Groups 1-2, and Comparative Examples 1-2 were dissolved in NMP solvent with conductive carbon black and polyvinylidene fluoride at a mass ratio of 85:10:5 under vacuum to prepare positive electrode slurries with a solid content of 80% by weight. These slurries were then coated, dried, and stamped to obtain positive electrode discs. Lithium-ion batteries were then prepared in the following order: positive electrode shell - positive electrode disc - separator - negative electrode disc - stainless steel sheet - spring sheet - negative electrode shell. The electrolyte was a 1 mol / L LiPF6 / EC:DMC solution (volume ratio 1:1) with 10% (volume fraction) fluoroethylene carbonate (FEC). The separator was a polypropylene microporous membrane. Lithium-ion batteries from Examples 1-5, Comparative Examples 1-2, and Control Groups 1-2 were prepared. The battery performance of each example, comparative example, and control group is shown in Table 1.

[0228] Table 1 Physicochemical data of each embodiment, comparative example, and control group

[0229]

[0230]

[0231] Note: Table 1 has two values ​​for the first sintering temperature. The first value is the temperature at which the material is heated from room temperature to the first temperature (temperature range of 800℃-1000℃), and the second value is the temperature at which the material is heated from the first temperature to the second temperature (temperature range of 900℃-1150℃) after holding at the first temperature for 10 hours.

[0232] As can be seen from Table 1 above:

[0233] 1. In Examples 1, 2, and 5, when the particle size D50 of the cobalt hydroxyl oxide-cobalt tetroxide composite material is not significantly different, as the content of cobalt hydroxyl oxide in the product increases, the density decreases. This is manifested in the overall average pore size of the sintered cobalt tetroxide increasing, the overall porosity increasing, and the tap density decreasing. This results in a decrease in the compaction density of the inherited cathode material, and the capacity performance of the battery prepared in the end shows a downward trend.

[0234] 2. In Examples 1, 2, 3 and 5, as the content of cobalt hydroxyl oxide in the cobalt hydroxyl oxide-cobalt tetroxide composite material increases, when sintering into cobalt tetroxide, the primary cobalt hydroxyl oxide particles, which serve as the framework, obtain uniformly distributed pores during the sintering transformation into primary cobalt tetroxide particles. This improves the reactivity of the lithium cobalt oxide cathode material during sintering, causing the sintering temperature to decrease and reducing energy consumption.

[0235] 3. Compared to Examples 1-5, Comparative Example 1, which uses cobalt carbonate, showed a decrease in tap density of cobalt tetroxide after sintering of 0.53-0.99 g / cm³. 3This resulted in a decrease in the compaction density of the inherited cathode material, lithium cobalt oxide, ultimately leading to a 16-25 mAh / g reduction in the first-cycle discharge capacity at 0.1C; and the overall porosity of Comparative Example 1 increased by 12.4-18.0%. The excessive porosity caused the lithium cobalt oxide cathode material to be prone to cracking during charging and discharging, ultimately resulting in a 1-5% reduction in the 50-cycle retention rate.

[0236] 4. Compared with Examples 1-5, the proportion of cobalt hydroxyl oxide in Control Groups 1 and 2 was too high, resulting in a decrease in tap density and excessive porosity of the sintered cobalt tetroxide product, leading to a decrease in the specific capacity of the corresponding cathode material, lithium cobalt oxide. In particular, under the same particle size, compared with Examples 3 and 4, the overall porosity of the sintered cobalt tetroxide in Control Group 1 increased by 3.2%, and the first-cycle discharge capacity at 0.1C decreased by 9 mAh / g; the overall average pore size increased by 23 nm, ultimately resulting in a 4% decrease in the 50-cycle retention rate, which was significant.

[0237] 5. Compared with Examples 1-5, the proportion of cobalt tetroxide in the cobalt hydroxyl oxide-cobalt tetroxide composite material of Comparative Example 2 is too high, which increases the calcination temperature required for the cathode material, reduces the reactivity, and leads to a decrease in the specific capacity of the corresponding cathode material. Ultimately, this results in a 4-13 mAh / g reduction in the first-cycle discharge capacity at 0.1C. Furthermore, the excessive proportion of cobalt tetroxide in Comparative Example 2 results in a small proportion of cobalt hydroxyl oxide as the framework. Its secondary particles are composed of multiple small spheres aggregated together, with multiple deep grooves between the spheres. The bonding is relatively loose, making the cathode material prone to cracking during charge and discharge after sintering. Ultimately, this leads to a 4-8% reduction in the 50-cycle retention rate.

[0238] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A cobalt hydroxyl oxide-cobalt tetroxide composite material, characterized in that, The secondary particles of the cobalt hydroxyl oxide-cobalt tetroxide composite material include multiple primary cobalt tetroxide particles and multiple primary cobalt hydroxyl oxide particles, wherein the multiple primary cobalt tetroxide particles fill the gaps formed between the multiple cobalt hydroxyl oxide particles; The molecular formula of the cobalt hydroxyl oxide-cobalt tetroxide composite material is aCoOOH•bCo3O4, wherein the mass ratio of a to b is 2:8-8:

2.

2. The cobalt hydroxyl oxide-cobalt tetroxide composite material according to claim 1, characterized in that, At least one of the following conditions must be met: A. In the cobalt hydroxyl oxide-cobalt tetroxide composite material, cobalt tetroxide has a spinel structure; B. The primary cobalt hydroxyoxide particles in the cobalt hydroxyoxide-cobalt tetroxide composite material are plate-shaped; D. The secondary particles of the cobalt hydroxyl oxide-cobalt tetroxide composite material are spherical or near-spherical; E. The particle size distribution (D90-D10) / (D90+D10) of the cobalt hydroxyl oxide-cobalt tetroxide composite material is 1.2-1.7; F. The particle size D50 of the cobalt hydroxyl oxide-cobalt tetroxide composite material is 3-16 μm; G. The tap density of the cobalt hydroxyl oxide-cobalt tetroxide composite material is 2.8-3.4 g / cm³. 3 .

3. The cobalt hydroxyl oxide-cobalt tetroxide composite material according to claim 2, characterized in that, The plate-shaped primary particles of cobalt hydroxyoxide are arranged in a disordered manner.

4. The cobalt hydroxyl oxide-cobalt tetroxide composite material according to claim 2, characterized in that, The particle size D50 of the cobalt hydroxyoxide-cobalt tetroxide composite material is 3-10 μm.

5. A cobalt tetroxide, characterized in that, The raw material for the cobalt tetroxide includes the cobalt hydroxyl oxide-cobalt tetroxide composite material as described in any one of claims 1-4.

6. The cobalt tetroxide according to claim 5, characterized in that, At least one of the following conditions must be met: H. The particle size distribution (D90-D10) / (D90+D10) of the cobalt tetroxide is 1.2-1.7; I. The particle size D50 of the cobalt tetroxide is 3-16 μm; J. The tap density of the cobalt tetroxide is 2.8-3.4 g / cm³. 3 ; K. The overall average pore size of the cobalt tetroxide is 20-120 nm; L. The overall porosity of the cobalt tetroxide is 3-10%; M. The specific surface area of ​​the cobalt tetroxide is 1.7-4.5 m². 2 / g.

7. The cobalt tetroxide according to claim 6, characterized in that, The particle size D50 of the cobalt tetroxide is 3-10 μm.

8. A method for preparing the cobalt hydroxyl oxide-cobalt tetroxide composite material according to any one of claims 1-4, characterized in that, include: A solution including cobalt solution, precipitant, oxidant and complexing agent is added to the bottom liquid. After reaction, cobalt hydroxyl oxide-cobalt tetroxide slurry is obtained. Solid-liquid separation is performed to obtain the cobalt hydroxyl oxide-cobalt tetroxide composite material.

9. The method for preparing the cobalt hydroxyl oxide-cobalt tetroxide composite material according to claim 8, characterized in that, At least one of the following conditions must be met: a. The cobalt solution comprises an aqueous solution of cobalt chloride and / or an aqueous solution of cobalt sulfate, wherein the mass concentration of cobalt ions in the cobalt solution is 90-130 g / L; b. The precipitant includes an aqueous solution of sodium hydroxide; c. The complexing agent includes EDTA-2Na and / or ammonia; d. The oxidant includes one or more of air, oxygen, and hydrogen peroxide with a volume fraction of 10-30%; f. The base solution comprises a precipitant and water, and the pH of the base solution is 10-12; g. The amount of the base liquid used accounts for 5-50% of the usable volume of the reaction vessel; h. The pH of the reaction is 9-12, and the temperature of the reaction is 50-80℃; i. The flow rate of the cobalt solution is 0.5-8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 2-6% / h of the available volume of the reaction vessel; j. The cobalt solution further includes a dopant compound, wherein the dopant element includes one or more of Al, Zr, Ti, Mg, Y, La, W, Ni, and Mn.

10. The method for preparing the cobalt hydroxyl oxide-cobalt tetroxide composite material according to claim 9, characterized in that, The air is compressed air, and the flow rate of the compressed air is 200-1000% / h of the usable volume of the reaction vessel; the flow rate of the oxygen is 40-200% / h of the usable volume of the reaction vessel; and the flow rate of the hydrogen peroxide is 0.5-4% / h of the usable volume of the reaction vessel.

11. A method for preparing cobalt tetroxide according to any one of claims 5-7, characterized in that, It is sintered from the cobalt hydroxyl oxide-cobalt tetroxide composite material as described in any one of claims 1-4.

12. A lithium cobalt oxide, characterized in that, The raw materials for the lithium cobalt oxide include a lithium source, and cobalt hydroxyl oxide-cobalt tetroxide as described in any one of claims 1-4 and / or cobalt tetroxide as described in any one of claims 5-7.

13. The lithium cobalt oxide according to claim 12, characterized in that, At least one of the following conditions must be met: k. The molar ratio of the sum of the molar amounts of cobalt and doping elements in the cobalt tetroxide to the molar ratio of lithium in the lithium source is 1:(1.02-1.06).

1. The lithium cobalt oxide is obtained from the raw material of the lithium cobalt oxide through a first sintering and a second sintering; m. When condition l is met, the first sintering includes: heating the lithium cobalt oxide raw material from room temperature to 600℃-900℃, holding it at that temperature for 2h-10h, then heating it to 900℃-1150℃, holding it at that temperature for 5h-20h, and then cooling it. The second sintering process includes: heating the material obtained from the first sintering from room temperature to 900℃-1100℃, holding it at that temperature for 5h-20h, and then cooling it.

14. A lithium battery, characterized in that, The raw materials for the lithium battery include lithium cobalt oxide as described in claim 12 or 13.

15. A lithium battery device, characterized in that, Including the lithium battery as described in claim 14.

Citation Information

Patent Citations

  • Preparation method of spherical hydroxyl cobaltous oxide-cobaltosic oxide composite material

    CN104716303A

  • Spherical tricobalt tetraoxide preparation method

    CN104986807A

  • Cobaltosic oxide, preparation method thereof and lithium ion battery

    CN113697865A